2011
DOI: 10.1063/1.3644393
|View full text |Cite
|
Sign up to set email alerts
|

Insight into unusual impurity absorbability of GeO2 in GeO2/Ge stacks

Abstract: Adsorbed species and its diffusion behaviors in GeO2/Ge stacks, which are future alternative metal-oxide-semiconductor (MOS) materials, have been investigated using various physical analyses. We clarified that GeO2 rapidly absorbs moisture in air just after its exposure. After the absorbed moisture in GeO2 reaches a certain limit, the GeO2 starts to absorb some organic molecules, which is accompanied by a structural change in GeO2 to form a partial carbonate or hydroxide. We also found that the hydrogen distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The thermal desorption spectra of molecules desorbed from the thermally grown GeO 2 and SiO 2 films indicated that GeO 2 has an unusual characteristic in terms of its absorbability of water molecules in air. 14,15 This strongly implies that the absorbance of moisture is the origin of the change in DE GeO 2 upon air exposure as shown in Figs. 2(a) and 2(b).…”
Section: B Ap-xps Experimentsmentioning
confidence: 94%
See 3 more Smart Citations
“…The thermal desorption spectra of molecules desorbed from the thermally grown GeO 2 and SiO 2 films indicated that GeO 2 has an unusual characteristic in terms of its absorbability of water molecules in air. 14,15 This strongly implies that the absorbance of moisture is the origin of the change in DE GeO 2 upon air exposure as shown in Figs. 2(a) and 2(b).…”
Section: B Ap-xps Experimentsmentioning
confidence: 94%
“…This agrees with the result of a dynamic SIMS analysis of an air-exposed GeO 2 /Ge sample, in which a certain amount of hydrogen was detected near the GeO 2 /Ge interface. 15 It is likely that infiltrated water molecules promote hydroxylation to generate hole-trap states in the GeO 2 films, especially near the GeO 2 /Ge interface or in the suboxide layer. These traps above the Ge Fermi level in the suboxide layer are positively charged by the electrons emitted to the Ge bulk, as suggested by Oniki and Ueno.…”
Section: B Ap-xps Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19] All these results point to a different effect of FGA on dielectric stacks prepared on Ge in comparison with SiO 2 /Si. Hints of the mechanisms underlying H incorporation in GeO 2 were provided by Ogawa and coworkers, 20 who investigated the depth distribution of H within GeO 2 films. They observed high amounts of H incorporated at the GeO 2 /Ge interfacial region, as result of thermal treatments under a humid atmosphere.…”
mentioning
confidence: 99%